1994
DOI: 10.7326/0003-4819-120-3-199402010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Hypertrophic Osteoarthropathy in Human Skeletal Remains from Pre-Hispanic Mesoamerica

Abstract: Hypertrophic osteoarthropathy is one of the earliest recognized disease entities in the history of medicine. It has a peculiar periosteal proliferation distinctive from other bone diseases. In its advanced stage, it leaves an indelible mark on the skeleton. It has been recently shown that digital clubbing is accompanied by a bone remodeling process of the underlying phalanges. Thus, theoretically, this entity can be recognized in ancient human skeletal remains. We studied part of the collection of skeletal rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…There is archaeological evidence of its occurrence even in the ancient world, and it was almost certainly described by Hippocrates (Martinez-Lavin et al, 1994). Hypertrophic osteopathy, generally abbreviated as HO, is also known by different names, including hypertrophic osteoarthropathy, hypertrophic pulmonary osteopathy, hypertrophic pulmonary osteoarthropathy, pulmonary osteoarthropathy, osteoporosis deformans, achropachia, Marie's disease and Pierre MarieBamberger syndrome (Lenehan and Fetter, 1985;Piermattei et al, 2006;Armstrong et al, 2007).…”
Section: What Is Hypertrophic Osteopathy (Review Of the Literature)mentioning
confidence: 99%
“…There is archaeological evidence of its occurrence even in the ancient world, and it was almost certainly described by Hippocrates (Martinez-Lavin et al, 1994). Hypertrophic osteopathy, generally abbreviated as HO, is also known by different names, including hypertrophic osteoarthropathy, hypertrophic pulmonary osteopathy, hypertrophic pulmonary osteoarthropathy, pulmonary osteoarthropathy, osteoporosis deformans, achropachia, Marie's disease and Pierre MarieBamberger syndrome (Lenehan and Fetter, 1985;Piermattei et al, 2006;Armstrong et al, 2007).…”
Section: What Is Hypertrophic Osteopathy (Review Of the Literature)mentioning
confidence: 99%
“…X-ray examination of La Ferrassie 1 shows no such loss of cortical bone. Hypervitaminosis A and flurosis affect the axial skeleton (Martinez-Lavin et al, 1994) and do not fit the pattern of lesions exhibited by La Ferrassie 1. Periosteal proliferation of the long bones may also result from fractures or burns at the site of bone repair (Cook, 1975).…”
Section: Differential Diagnosis Of the Periosteal Lesionsmentioning
confidence: 99%
“…It may also be a result of an altered blood flow pattern where impairment of the peripheral circulation may result in periosteal new bone formation (secondary hypertrophic osteoarthropathy). Chronic venous stasis is found in older persons and the bone changes are limited to the lower extremities (Martinez-Lavin et al, 1994).…”
Section: Differential Diagnosis Of the Periosteal Lesionsmentioning
confidence: 99%
“…Although HOA usually displays bilaterally symmetrical lesions, bilateral symmetry is not universal (Rothschild and Rothschild, 1998;Assis et al, 2011). In other studies, skeletal remains of a young adult woman found at burial site 23 during the exploration of Jaina (Mexico), and now curated at the Physical Anthropology Department of the National Museum of Anthropology of Mexico City (Martinez-Lavin et al, 1994), has a fibula with advanced periosteal new bone formation that was diagnosed as HOA. In a second report, Christensen et al, 2013 described an adult male exhumed at the medieval site of Zalavár in South-West Hungary which has tibial and fibular lesions that are morphologically similar to those of our subject, and also was diagnosed with HOA.…”
Section: Discussionmentioning
confidence: 99%